DECREASING OF ROAD TRAFFIC ACCIDENTS RATE WITHE THE ASSISTANCE OF INTELLIGENT VEHICLE - Cernicky, Lubomir; Kalasova, Alica (Doprava a spoje, 2012)
The article deals with road traffic accidents and with possible ways of decreasing numbers of fatalities by using intelligent transport systems in cars. The beginning of the article includes road fatalities evolution in European Union and there are outlined some possible reasons of the evolution. Second part is about European Union policy, where the aim of halving fatalities on European roads till 2020 is included in. Next part describes some of ITS application used in cars. The efficiencies of selected ITS applications are described too.